Phenolic compounds and polysaccharides in the date fruit (Phoenix dactylifera L.): Comparative study on five widely consumed Arabian varieties. (30th November 2022) - Khatib, Mohamad; Al-Tamimi, Amal; Cecchi, Lorenzo; Adessi, Alessandra; Innocenti, Marzia; Balli, Diletta; Mulinacci, Nadia
Highlights: Two polysaccharides fractions were collected after fruit decoction and centrifugation. Hydrodynamic volumes of polysaccharides evaluated by DLS were from 237 nm to 425 nm. Galacturonic acid ranged from 28.3% to 40.3% in PF1 and from 14.5% to 22.3% in PF2. The highest methylation degree was for the PF1 fractions, from 56% to 83% The highest acylation degree was from 47 to 68 % for the less soluble PF2 fractions. Abstract: The study analysed polysaccharides and phenolic compounds in widely consumed but little studied date fruits varieties such as Sukkari, Ajwa, Segae, Barrny and Khalas harvested at Tamr stage. The total phenols were in similar amount in the five varieties and ranged from 20 to 50 mg/100 g DW. The decoction and successive centrifugation made it possible to collect two main polysaccharide fractions for all the selected fruits. For each variety the first fraction was more abundant, with a lower swelling capacity and a higher amount of galacturonic acid (28.3% to 40.1%). The second fraction was only soluble in alkaline solution, with an average galacturonic acid content of only 17%. The different structure of the two polysaccharide fractions was also confirmed by the composition in neutral sugars and the degrees of methylation and acetylation. The proposed extraction procedure could be applied for larger scale extraction of the date fruit polysaccharides.